Agro ecological base differences of village based local chicken performance and household product consumption in Amhara Region, Ethiopia - Habtamu Ayalew; Demissie Chanie; Tewodros Fentahun; Asmamaw Yinnesu; Yohannes Dagnew; Dehinasew Moges (Cogent Food & Agriculture, 2023)
AbstractThe study was conducted to describe village-based local chicken performance, major husbandry practices, and product consumption habits of households in an agro ecological base. Multi-stage sampling techniques were applied for this study. Semi-structured questionnaire, field observation, and key informant interview methods of data collection were used. The majority of households (71.00%) were providing supplementary feed for their chickens. Feed supplementation practices in the lowland areas were significantly lower (p < 0.05) and accounted for 46.24% of respondents. In the study area, 57.33% of respondents were faced disease problems which were significantly higher (p < 0.05) in lowland areas. Most of respondents (81.67%) used ethno veterinary to treat their ill chickens. Annual egg production/hen, number of eggs/hen/clutch, number of clutches/hen/year, age of cockerels at first mating, pullets at first egg laying, number of egg set/brooding were 61.91 ± 5.70, 14.34 ± 1.69, 3.44 ± 0.44, 5.76 ± 0.68 months, 6.26 ± 0.26 months, and 11.95 ± 1.55, respectively. The survey also indicated that survived chick to market age (66.45 ± 6.83%), male age at slaughter (9.16 ± 1.02 months), number of eggs hatched per incubation (9.60 ± 1.36), and hatchability percentage were 79.90 ± 4.48%. The number of eggs consumed/per capita/year, and average numbers of slaughtered chickens/year for home consumption were 46.54 ± 29.44, and 1.46 ± 1.50, respectively, which were significantly lower (P < 0.05) in lowland areas. Generally, most of the performances of local chickens and chicken product consumption habits were poor in the areas. Therefore, agro ecological base improvement intervention about breed, feeds and feeding strategies, health care management, and awareness of households on product utilization are vital in the study area.